2019
DOI: 10.1002/cbdv.201900017
|View full text |Cite
|
Sign up to set email alerts
|

Profiling Auspicious Butyrylcholinesterase Inhibitory Activity of Two Herbal Molecules: Hyperforin and Hyuganin C

Abstract: Cholinergic therapy based on cholinesterase (ChE) inhibitory drugs is the mainstay for the treatment of Alzheimer's disease. Therefore, an extensive research has been continuing for the discovery of drug candidates as inhibitors of acetyl‐ and butyrylcholinesterase. In this study, two natural molecules, e. g. hyperforin and hyuganin C were tested in vitro for their AChE and BChE inhibitory activity. Both of the compounds were ineffective against AChE, whereas hyperforin (IC50=141.60±3.39 μm) and hyuganin C (IC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…The IC 50 value of PJ5 in this study was lower than those of broussonin A (7.50 µM) from Anemarrhena asphodeloides a 42 , isoacteoside (29.7 µM) from H. procumbens 52 , corenone B (10.9 μg/mL, i.e., 49.5 µM) from Niphogeton dissecta 60 , and kaempferol (62.5 µM) from Cleistocalyx operculatus 61 , but higher than that of 4′-hydroxy Pd–C-III (5.78 µM) from A. decursiva 58 . Compared to other coumarins, the IC 50 value of PJ5 for BChE inhibition was lower than those of hyuganin C (38.86 µM), from Mutellina purpurea 62 , a coumarin pteryxin (12.96 μg/mL, i.e., 33.5 µM) from M. purpurea 63 , the esculetin (9.29 µM) and the daphnetin (8.66 µM) 56 , and it might be concluded that PJ5 is the most potent BChE inhibitor in natural coumarins reported.…”
Section: Discussionmentioning
confidence: 73%
“…The IC 50 value of PJ5 in this study was lower than those of broussonin A (7.50 µM) from Anemarrhena asphodeloides a 42 , isoacteoside (29.7 µM) from H. procumbens 52 , corenone B (10.9 μg/mL, i.e., 49.5 µM) from Niphogeton dissecta 60 , and kaempferol (62.5 µM) from Cleistocalyx operculatus 61 , but higher than that of 4′-hydroxy Pd–C-III (5.78 µM) from A. decursiva 58 . Compared to other coumarins, the IC 50 value of PJ5 for BChE inhibition was lower than those of hyuganin C (38.86 µM), from Mutellina purpurea 62 , a coumarin pteryxin (12.96 μg/mL, i.e., 33.5 µM) from M. purpurea 63 , the esculetin (9.29 µM) and the daphnetin (8.66 µM) 56 , and it might be concluded that PJ5 is the most potent BChE inhibitor in natural coumarins reported.…”
Section: Discussionmentioning
confidence: 73%
“…As regards other natural compounds, inhibition of BChE by GC was greater than that by boldine (IC 50 = 321 µM) [ 45 ], hyperforin and hyuganin C (IC 50 = 141.60 and 38.86 μM, respectively) [ 46 ], cremaphenanthrene F (14.62) [ 47 ], scopoletin (IC 50 = 9.11 µM) [ 48 ], and broussonin A and sagachromanol I (IC 50 = 7. 50 and 10.79 µM, respectively) [ 49 ], but less than those of norditerpenoids isograndifoliol and (1 R ,15 R )-1-acetoxycryptotanshinone (IC 50 = 0.9 and 2.4 µM, respectively) [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…SH-SY5Y cells were seeded at an initial density of 5 × 10 3 cells/well in 96-well plates and allowed to attach overnight in DMEM/F12 medium with necessary supplementation. The cells were treated with solvent (DMSO), as a control, and varying concentrations of test compounds (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). Then, the cells were incubated in humidified 5 % CO 2 atmosphere at 37 °C.…”
Section: Cell Viability Assaymentioning
confidence: 99%
“…Chemical structures of the coumarin derivatives(1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16).…”
mentioning
confidence: 99%
See 1 more Smart Citation